Tuberculosis prevention in South Africa. - Gwenan M Knight; Peter J Dodd; Alison D Grant; Katherine L Fielding; Gavin J Churchyard; Richard G White (PLoS ONE, 2015)
Background South Africa has one of the highest per capita rates of tuberculosis (TB) incidence in the world. In 2012, the South African government produced a National Strategic Plan (NSP) to control the spread of TB with the ambitious aim of zero new TB infections and deaths by 2032, and a halving of the 2012 rates by 2016. Methods We used a transmission model to investigate whether the NSP targets could be reached if immediate scale up of control methods had happened in 2014. We explored the potential impact of four intervention portfolios; 1) "NSP" represents the NSP strategy, 2) "WHO" investigates increasing antiretroviral therapy eligibility, 3) "Novel Strategies" considers new isoniazid preventive therapy strategies and HIV "Universal Test and Treat" and 4) "Optimised" contains the most effective interventions. Findings We find that even with this scale-up, the NSP targets are unlikely to be achieved. The portfolio that achieved the greatest impact was "Optimised", followed closely by "NSP". The "WHO" and "Novel Strategies" had little impact on TB incidence by 2050. Of the individual interventions explored, the most effective were active case finding and reductions in pre-treatment loss to follow up which would have a large impact on TB burden. Conclusion Use of existing control strategies has the potential to have a large impact on TB disease burden in South Africa. However, our results suggest that the South African TB targets are unlikely to be reached without new technologies. Despite this, TB incidence could be dramatically reduced by finding and starting more TB cases on treatment.